2010
DOI: 10.2353/ajpath.2010.090552
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs May Mediate the Down-Regulation of Neurokinin-1 Receptor in Chronic Bladder Pain Syndrome

Abstract: Bladder pain syndrome (BPS) is a clinical syndrome of pelvic pain and urinary urgency-frequency in the absence of a specific cause. Investigating the expression levels of genes involved in the regulation of epithelial permeability , bladder contractility , and inflammation , we show that neurokinin (NK)1 and NK2 tachykinin receptors were significantly down-regulated in BPS patients. Tight junction proteins zona occludens-1 , junctional adherins molecule -1 , and occludin were similarly down-regulated , implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 68 publications
8
85
1
2
Order By: Relevance
“…The UA group consisted of patients with weak detrusor contractions (UA) or patients with acontractile detrusor and cystoscopy in line with obstruction. In all groups, 4 urothelium-covered muscle-containing biopsies were collected from the bladder dome by the same urologist and total RNA was isolated as described previously (12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The UA group consisted of patients with weak detrusor contractions (UA) or patients with acontractile detrusor and cystoscopy in line with obstruction. In all groups, 4 urothelium-covered muscle-containing biopsies were collected from the bladder dome by the same urologist and total RNA was isolated as described previously (12).…”
Section: Resultsmentioning
confidence: 99%
“…Normalized Ct values for 3-mRNA or 3-miRNA signatures of the samples with the known urodynamic status ( Figure 5, E and F) were employed in machine-based learning algorithms described in the Methods to train the model. Using the Ct values for either mRNA or miRNA signatures of the blinded samples as an input, the model allocated them to 3 groups corresponding to the predicted bladder functional state: BOO7, 24, 31, 32, 37, 38, 39, 40, 6, 5, 21, 22 and 23 belonged to the DO group; BOO16, 14, 15, 9, 8, 33, and 34 belonged to the BO group, and the remaining samples (BOO28, 29,30,41,42,10,11,12,13,17,18,19,20,4,3,2,1,25,26,27) were from the UA group. On the heatmaps, the samples were colored according to the machine-based group allocation (DO in blue, BO in green, and UA in orange) ( Figure 6, A and B).…”
Section: Ua (mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, neuropathic pain generally involves the altered expression of many genes (Lacroix-Fralish et al, 2007) and it is likely that other genes in addition to Gad1 are also the targets of persistent pain-induced chromatin remodeling. GAD65 is another key rate-limiting-rate and is targeted preferentially to presynaptic terminals of central neurons for GABA synthesis (Tian et al, 1999;Patel et al, 2006). Studies have showed that GAD65 in different regions could participate in pain regulation by decreasing inhibition among neurons through reducing the levels of cellular GABA (Gwak and Hulsebosch, 2011;Zhang et al, 2011;Lorenzo et al, 2014).…”
Section: Role Of Gad67 In the Spinal Dorsal Horn In Neuropathic Painmentioning
confidence: 99%
“…However, in lower urinary tract dysfunction, this process is impaired by symptoms of urgency, frequency, and incomplete emptying. Lower urinary tract dysfunction causes profound changes in the gene expression profiles of both bladder urothelium and smooth muscle: in human bladder pain syndrome (BPS) 2 patients, the proteoglycan core proteins (1) and the tight junction proteins ZO-1, junctional adhesion molecule 1, and occludin (2) were down-regulated, implicating increased urothelial permeability. Bladder smooth muscle has a high level of plasticity and undergoes remodeling during lower urinary tract dysfunctions (3,4).…”
mentioning
confidence: 99%